A comparison of the heat treatment duration and the multilayered effects on the poly(lactic) acid braid reinforced calcium phosphate cements used as bone tissue engineering scaffold. (May 2017) - Chen, Wen-Cheng; Chen, Jian-Chih; Ko, Chia-Ling; Yang, Jia-Kai; Huang, Chien-Lin; Lou, Ching-Wen; Lin, Jia-Horng
Composites comprising a braided poly(lactic) acid (PLA) filament and calcium phosphate bone cement (CPC) were inferred to maintain space and to pack porous fillers into restorative sites. Composites of alkalized multilayer-PLA braids and CPC (PLA/CPC) were divided into various groups according to a series of heat-treatment periods that lasted for 60, 90, 120, 150, and 180 min at 160℃; subsequently, these composites were characterized. Strength decays of samples were also compared after 24 h immersion in Hanks's physiological solution. Results showed that the PLA/CPC specimens were toughened after treatment at 160℃ for 120 min. Furthermore, the moduli of PLA/CPC groups increased significantly when the heating time was more than 150 min; this effect was generated by the cold crystallization within the PLA filaments. The reduced stress in the composites after immersion was attributed to the fibers that protruded from the scaffold surface and to hydrolysis. The mechanical test results for the PLA/CPC composites indicated that the toughening effect was strengthened significantly under prolonged heat treatment, especially when the heating time was longer than 150 min. The cold crystallization degree of PLA increased, thereby enhancing the strength and toughness of a specimen before immersion. Thus, PLA/CPC composites can be used to simulate potential bone functions as well as to maintain three-dimensional spaces and pack porous fillers into restorative sites conveniently.